Extended Abstracts of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411763.3451780
|View full text |Cite
|
Sign up to set email alerts
|

EnergyVis: Interactively Tracking and Exploring Energy Consumption for ML Models

Abstract: Figure 1: The EnergyVis user interface, with multiple coordinated views. (A) The Model Energy Profile View allows users to select an energy profile of pre-loaded models, generate new profiles (for models that a user wishes to train), and import saved profiles. (B) The Consumption Chart allows users to view the energy and carbon consumption of their selected model. (C) Using the Model Region view, users can view the region where a model was trained, and select regions with a lower energy intensity as an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…However, recent work has found that their results vary significantly and are not fully representative of the true emissions incurred by training [3]. Perhaps most similar to our work, EnergyVis [41] is an interactive tool for visualizing and comparing energy consumption of ML models as a function of hardware and physical location (U.S. state), given metadata about a model's energy use per epoch. Other studies have gone beyond simply tracking the emissions from training models, aiming to quantify the emissions resulting from manufacturing computing hardware [15], the broader impacts of sustainable AI [49], and the methodologies used to assess those impacts [21,26].…”
Section: Related Workmentioning
confidence: 61%
See 1 more Smart Citation
“…However, recent work has found that their results vary significantly and are not fully representative of the true emissions incurred by training [3]. Perhaps most similar to our work, EnergyVis [41] is an interactive tool for visualizing and comparing energy consumption of ML models as a function of hardware and physical location (U.S. state), given metadata about a model's energy use per epoch. Other studies have gone beyond simply tracking the emissions from training models, aiming to quantify the emissions resulting from manufacturing computing hardware [15], the broader impacts of sustainable AI [49], and the methodologies used to assess those impacts [21,26].…”
Section: Related Workmentioning
confidence: 61%
“…Improving the carbon transparency of research and practice. Despite the existence of tools such as Code Carbon [38] and EvergyVis [41], both carbon estimation and reporting in ML publications and technical reports remain a relatively rare phenomenon. Conferences such as NeurIPS and NAACL have recently added emissions reporting as an optional part of the submission process; however, more encouragement will be necessary for this to become commonplace.…”
Section: Future Directionsmentioning
confidence: 99%
“…When DiSalvo et al [22] analysed the SHCI landscape in 2010, they classifed 45% of it as persuasive technology, for which "the standard approach is to design systems that attempt to convince users to behave in a more sustainable way". This is not echoed in our corpus, which contains only one study that uses an openly persuasive approach [77]; a few other studies have an indirect persuasive element as they encourage refection [15], support learning [19,20] or raise awareness [76]. What we see instead is a substantial amount of speculative design (e.g.…”
Section: Speculation Instead Of Prescriptionmentioning
confidence: 84%
“…What we see in our corpus is that energy has remained a key theme (e.g. [60,76,81,89,90]), although the research approaches and contexts have changed, as described above. A subcluster of energy-related research explores the carbon footprint and, more generally, the (un)sustainability of digital technology.…”
Section: Diverse Explorations Beyond Resource Consumptionmentioning
confidence: 99%
“…In [47], the authors propose a framework to investigate carbon emissions of end-to-end automatic speech recognition (ASR). EnergyVis [59] is a more general tool, which is capable of tracking energy consumption for various kinds of machine learning models and provides an interactive view to compare the consumption across different locations. Unfortunately, it is limited to the USA at the moment.…”
Section: Practical Suggestions: How To Quantify Environmental Impact?mentioning
confidence: 99%